How Wellcome's opaque fossil fuel investments harm its global health mission. (19th May 2021) - Schwab, Tim
Abstract : The Wellcome Trust's commitment to tackle the health impacts of carbon emissions is threatened by its own lingering investments in the fossil fuel industry. So why does it continue to shun calls to divest while raising the status of climate change in its strategy? Tim Schwab reports